2008
DOI: 10.1080/02713680802344708
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Caffeine on Retrobulbar Hemodynamics

Abstract: The vascular resistance of the retrobulbar vessels appears to be altered by caffeine consumption. Further studies are needed to investigate the effects of caffeine on hemodynamics in patients with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 27 publications
1
40
3
1
Order By: Relevance
“…It is also the first trial to examine OPA after caffeine consumption. Other strengths include the wider 40-89-year-old age range and older 64-year-old mean age of our subjects, compared with the 20-44-year-old age range and approximately 25 year mean age of subjects in the other trials combined, 25,28,29,33,34,37 as the risk of POAG increases after age 40. The study's crossover design minimized individual variations, enhancing its power.…”
Section: Eyementioning
confidence: 99%
See 3 more Smart Citations
“…It is also the first trial to examine OPA after caffeine consumption. Other strengths include the wider 40-89-year-old age range and older 64-year-old mean age of our subjects, compared with the 20-44-year-old age range and approximately 25 year mean age of subjects in the other trials combined, 25,28,29,33,34,37 as the risk of POAG increases after age 40. The study's crossover design minimized individual variations, enhancing its power.…”
Section: Eyementioning
confidence: 99%
“…The study's crossover design minimized individual variations, enhancing its power. Unlike other RCTs, we did not exclude subjects on antiglaucoma medications, 25,28,29,31,33,34 on systemic medications, 25,31 with a history of cataract surgery or glaucoma laser procedure before the 6 months preceding the study, 25,28,[31][32][33][34] with systemic hypertension, 25,29,31,34 with diabetes, 25,29 who currently smoke, 29,33 who have a family history of glaucoma 33,34 and who ingest beyond a certain daily level of caffeine. 25, 29 The absence of these exclusions enhanced the generalizability of our results.…”
Section: Eyementioning
confidence: 99%
See 2 more Smart Citations
“…Caffeine is a xanthine with known cardiovascular effects, such as increasing heart rate and increasing peripheral resistance by vasoconstriction (Bunker, 1979). A placebo-controlled trial in healthy individuals showed that the resistance index of ophthalmic; short posterior ciliary arteries and central retinal arteries were significantly increased after coffee ingestion (Ozkan, 2008). Despite its concomitant ability to mildly increasing IOP, a prospective study did not find an increased risk for primary open-angle glaucoma in average coffee drinkers (people consuming more than 5 cups a day had a small risk increase) (Kang, 2008).…”
Section: Systemic Medications and Other Measuresmentioning
confidence: 99%